Tubaramure, a food-assisted integrated health and nutrition program, reduces child stunting in Burundi: A cluster-randomized controlled intervention trial - Leroy, Jef L.; Olney, Deanna K.; Ruel, Marie T. (Oxford University Press, 2018)
We assessed the impact of Burundi's Tubaramure Food-assisted maternal and child health and nutrition (FA-MCHN) program on linear growth. The program targeted women and their children during the first 1000 d and included 1) food rations, 2) strengthening of health services and promotion of their use, and 3) behavior change communication (BCC). A second objective was to assess the differential effect when varying the timing and duration of receiving food rations.